Building Digital Purchase Decisions through the Synergy of E-Marketing Mix and Consumer Trust - Sukmadia Sumpena; Putu Nina Madiawati; Agus Maolana Hidayat (PT FORMOSA CENDEKIA GLOBAL, 2026)
The development of internet technologies has altered how individuals buy fashion things. Websites and mobile applications are becoming increasingly important to consumers for information searches, product comparisons, and purchasing. This change encourages many fashion businesses to enhance their official e-commerce platforms. However, high traffic does not always result in high sales conversion. This study examines how trust and the e-marketing mix affect purchase intention and decision using an official fashion e-commerce platform. The study employed a quantitative methodology, analysing data collected from clients who registered and made purchases through the company's mobile application or website using SEM-PLS. The findings demonstrate that while buying intention has the greatest impact on purchase decision, e-marketing mix and trust have a favourable and significant effect on purchase intention. Additionally, purchasing intention mediates the impact of both factors on the choice to buy.